Identification of three isoform patterns of human serum amyloid A protein. - Strachan, A F (1988)
Three patterns of human apo-SAA (serum amyloid A protein) isoforms have been identified by electrofocusing. In pattern 1, six major apo-SAA isoforms of pI 6.0, 6.4, 7.0, 7.4, 7.5 and 8.0 were found. In pattern 2, the apo-SAA isoforms of pI 7.4 and 8.0 were not detected, whereas in pattern 3 the pI-7.0 and -7.5 isoforms were lacking. Six patients displayed apo-SAA isoform pattern 1, 11 displayed pattern 2 and one displayed pattern 3.